Promoting Interoperability in Europe's E-Government. - Bovalis, Konstantinos; Peristeras, Vassilios; Abecasis, Margarida; Abril-Jimenez, Raul-Mario; Rodriguez, Miguel Alvarez; Gattegno, Corinne; Karalopoulos, Athanasios; Sagias, Ioannis; Szekacs, Szabolcs; Wigard, Suzanne (Computer (00189162), 2014)
To address a fragmented European e-government landscape, the Interoperability Solutions for Public Administrations (ISA) program has created a model for implementing interoperability solutions across technical, semantic, organizational, and legal levels, to the benefit of EU member states. The Web extra at http://youtu.be/O5myBgxxSfQ is a video showing how ISA fosters interoperability in various layers. This includes a number of initiatives for promoting semantic interoperability in Europe. Using a common metadata vocabulary or Asset Description Metadata Schema (ADMS), relevant assets can be searched and exchanged through the Federation on Joinup.